Urban geography - Diego, Ian (New York Murphy and moore, 2021)
The branch of geography concerned with the cities, urban life, built environment and urban processes is known as urban geography. It attempts to understand the flow of natural and economic resources, development of infrastructure, governance, institutional activities and socio-spatial inclusions and exclusions. Some of the major areas of study under this discipline are urban planning, urban anthropology and urban sociology. On the basis of their roles in the city system, urban geography classifies cities into central places and specialized-function cities, transportation cities.
Keywords: Geographical study of population; Urban growth; Demographic models